Antibiotic rotation for febrile neutropenic patients with hematological malignancies: clinical significance of antibiotic heterogeneity. - Yong Chong (PLoS ONE, 2013)
BACKGROUND: Our unit adopted the single administration of cefepime as the initial treatment for febrile episodes in neutropenic patients with hematological malignancies. However, recently, cefepime-resistant gram-negative bacteremia, including those with extended-spectrum β-lactamase (ESBL)-producers, was frequently observed in these patients. Therefore, we instituted a rotation of primary antibiotics for febrile neutropenic patients in an attempt to control antibiotic resistance. METHODS: This prospective trial was performed from August 2008 through March 2011 at our unit. After a pre-intervention period, in which cefepime was used as the initial agent for febrile neutropenia, 4 primary antibiotics, namely, piperacillin-tazobactam, ciprofloxacin, meropenem, and cefepime, were rotated at 1-month intervals over 20 months. Blood and surveillance cultures were conducted for febrile episodes, in order to assess the etiology, the resistance pattern (particularly to cefepime), and the prognosis. RESULTS: In this trial, 219 patients were registered. A 65.9% reduction in the use of cefepime occurred after the antibiotic rotation. In the surveillance stool cultures, the detection rate of cefepime-resistant gram-negative isolates, of which ESBL-producers were predominant, declined significantly after the intervention (8.5 vs 0.9 episodes per 1000 patient days before and after intervention respectively, P<0.01). Interestingly, ESBL-related bacteremia was not detected after the initiation of the trial (1.7 vs 0.0 episodes per 1000 patient days before and after intervention respectively, P<0.01). Infection-related mortality was comparable between the 2 periods. CONCLUSIONS: We implemented a monthly rotation of primary antibiotics for febrile neutropenic patients. An antibiotic heterogeneity strategy, mainly performed as a cycling regimen, would be useful for controlling antimicrobial resistance among patients treated for febrile neutropenia.